Revisiting the Open Government Phenomenon. A Meta-Analysis of the International Literature - Valenzuela Mendoza, Rafael Enrique (2018)
According to the contributions of several authors, the Open Government (OG) concept is maturing and moving toward its consolidation as a new field of multidisciplinary knowledge with its own dynamics. However, little is known about how it is developing that path, if it is really generating its own characteristics and what is its scope in terms of the creation of an academic community. This article makes a systematic review or meta-evaluation of the literature on OG for 5 years (2011 to 2015) of the three magazines most recognized for their production and quality of content in the theme: Government Information Quarterly, Information Polity and eJournal of eDemocracy and Open Government. This article analyzes a total universe composed of 189 articles, classified into different categories that try to answer three research questions: How is the OG analyzed? (Study Design, Research Techniques, Methodological Approach) Where is the OG analyzed? (University Departments, Host Country of the Universities and Institutions, Level of Government, Analyzed Country/Areas) What are the most analyzed topics and the most prominent concepts in the study of OG? (Main Topic, Keywords). Article data reveal the key features of OG analysis: still little quantitative and explicative-correlational studies, very focused on the countries of the Anglo-American area, and with very diverse interests ranging from open data, e-government to social media to co-production. In addition, with the latter, it can be confirmed to what extent a scientific community has been created around the OG as well as establishing some conclusions on the development of OG in the coming years.